The blue advantage: a novel blue carotenoprotein pigment in the tropical seastar Linckia laevigata is an antioxidant defence against extreme environmental stress - Suzanne T. Williams; Stephanie M. Heyworth; Yasunori Kano; Nicholas W. Roberts; Hugh F. Carter; Karen L. Cheney (Marine Biology, 2025)

Progress towards the control of invasive alien species in the Cape Floristic Region’s protected areas - Brian W. van Wilgen; Nicholas S. Cole; Johan Baard; Chad Cheney; Karen Engelbrecht; Louise Stafford; Andrew A. Turner; Nicola J. van Wilgen; Andrew M. Wannenburgh (Biological Invasions, 2025)
This paper assesses progress towards the control of biological invasions in 18 protected areas (PAs) covering 677 584 ha in the Cape Floristic Region (CFR), and whether progress has been sufficient to achieve Target 6 of the Kunming-Montreal Global Biodiversity Framework. We used eight indicators for assessing the inputs (quality of the regulatory framework, money spent and planning coverage for species and protected areas), outputs (species and protected areas treated), and outcomes (effectiveness of species and protected area treatments) of management. The estimated money spent over 13 years (2010–2022) was ZAR 976 million, or ZAR 75 million per year. Management plans for PAs were assessed as adequate over 78.5% of the area, but only six out of 226 regulated invasive species had species-specific control plans in place. A total of 567 alien species occurred in the CFR’s PAs, 226 of which were regulated species (i.e. species that had to be controlled), 126 (55.8%) of which received some management. Spending was highly skewed, with over 60% of all funding spent on trees and shrubs in the genus Acacia . Management efforts reached 24% of the land within the CFR’s protected areas, with higher coverage in national parks (60%) than in provincial nature reserves (9%). Management effectiveness was assessed as either permanent, effective or partially effective for 29 species (20 due to biological control), and ineffective for 25; for the remainder, there was either no management or effectiveness could not be evaluated. We conclude that some progress has been made with respect to controlling invasive alien species in the CFR, but that insufficient and declining funding remains a significant barrier to effective management. To increase efficiency, it will be necessary to secure additional funding from more diversified sources, make more use of biological control and prescribed fire, and regularly monitor the outcomes of management.

Automated workflows using Quantitative Colour Pattern Analysis (QCPA): a guide to batch processing and downstream data analysis - Cedric P. van den Berg; Nicholas D. Condon; Cara Conradsen; Thomas E. White; Karen L. Cheney (Evolutionary Ecology, 2024)
Animal and plant colouration presents a striking dimension of phenotypic variation, the study of which has driven general advances in ecology, evolution, and animal behaviour. Quantitative Colour Pattern Analysis (QCPA) is a dynamic framework for analysing colour patterns through the eyes of non-human observers. However, its extensive array of user-defined image processing and analysis tools means image analysis is often time-consuming. This hinders the full use of analytical power provided by QCPA and its application to large datasets. Here, we offer a robust and comprehensive batch script, allowing users to automate many QCPA workflows. We also provide a complimentary set of useful R scripts for downstream data extraction and analysis. The presented batch processing extension will empower users to further utilise the analytical power of QCPA and facilitate the development of customised semi-automated workflows. Such quantitatively scaled workflows are crucial for exploring colour pattern spaces and developing ever-richer frameworks for analysing organismal colouration accounting for visual perception in animals other than humans. These advances will, in turn, facilitate testing hypotheses on the function and evolution of vision and signals at quantitative and qualitative scales, which are otherwise computationally unfeasible.

Elevation-based probabilistic mapping of irregularly flooded wetlands along the northern Gulf of Mexico coast - Nicholas M. Enwright; Wyatt C. Cheney; Kristine O. Evans; Hana R. Thurman; Mark S. Woodrey; Auriel M.V. Fournier; Dean B. Gesch; Jonathan L. Pitchford; Jason M. Stoker; Stephen C. Medeiros (Remote Sensing of Environment, 2023)

Wavelet decomposition facilitates training on small datasets for medical image classification by deep learning - Axel H. Masquelin; Nicholas Cheney; C. Matthew Kinsey; Jason H. T. Bates (Histochemistry and Cell Biology, 2021)